Simulation study on photon generation and collection of tower applied to NICA-MPD electromagnetic calorimeter. (25th January 2022) - Peng, X.; Zhu, K.; Ji, X.; Xiao, M.; Luo, F.; Huang, Y.; Zhu, J.; Xiao, W.; Luo, S.; Liu, Y.; He, L.; Wang, X.
Abstract: Shashlik tower, which is composed of absorbers and scintillators alternately, surrounded by reflector and coupled with Silicon Photomultiplier (SiPM) by Wavelength-Shifting (WLS) fibers, is a significant component to measure the energy and position of photons and electrons in Electromagnetic Calorimeter (ECal), a key detector of the Multi Purpose Detector (MPD) at the Nuclotron-based Ion Collider facility (NICA) in Russia. In this paper, the effect of materials adopted for absorber, reflector and WLS fiber, the length and curvature of fibers and the electrons incident position on photons transmission performance of tower is simulated based on GEANT4 software. The impact of Gaussian deviation's electron beam energy and spread of 10% in the energy range on the energy resolution of tower is also studied. Results show that the low polishing degree absorber, the high polishing degree TiO_2 reflector and the type of Y-11 WLS fibers bent with a curvature radius of greater than 11 cm can significantly improve the light output. In addition, electrons injected along the centre of tower can make photons position distribution in SiPM more uniform. The generation time of photons in scintillators and time of arrival at the SiPM both obey the Landau distribution. Finally, the energy resolution of tower can be better than 3.8%/√(E) (GeV) for a Gaussian deviation's electron beam with an average energy of 3 GeV and spread of 10% in the energy range.